Impactos da hormonioterapia na qualidade de vida relacionada à saúde de mulheres com câncer de mama - Corpes, Erilaine de Freitas (2023)
Hormone therapy (HT) is a treatment modality for breast cancer offered to patients with positive hormone receptors, allowing greater flexibility, control over therapy and less interference in social life. However, like any treatment, HT can have a direct impact on the Health-Related Quality of Life (HRQOL). Thus, the present study aimed to evaluate the impact of HT on the HRQoL of women with breast cancer. An analytical cross-sectional study was developed in a reference mastology outpatient clinic of the public network, located in the city of Fortaleza/CE. The inclusion criteria were: age 18 years or older; diagnosis of breast cancer with expression of hormone receptors; under treatment with HT such as tamoxifen or aromatase inhibitor. Exclusion criteria were: being under chemotherapy and/or radiotherapy concomitant with HT; previous or current history of other cancers; impaired cognitive ability; and the presence of metastases. Thus, we obtained a total sample of 75 patients, who were divided into four subgroups according to the type of HT and time of use. Three instruments were used for data collection: one instrument to collect sociodemographic and clinical data; two HRQoL scales: Functional Assessment of Cancer Therapy - Breast (FACT-B) version 4.0 and Functional Assessment of Cancer Therapy - Endocrine Symptoms (FACT-ES) version 4.0. Measures of central tendency and dispersion were calculated for numerical variables, and absolute and relative frequencies for categorical variables. Nonparametric tests, such as Kruscal-Wallis and Pearson's r, were used. There was no variation in HRQL scores between the subgroups. However, when correlating the subgroups with the subscales and their total scores, statistically significant correlations were found. Physical well-being showed a direct and high correlation with all subgroups, whereas social/family well-being showed more weak correlations. The anastrozole group showed more significant correlations in the context of emotional, functional and social/family well-being. The symptoms most reported by the patients were: hot flashes, musculoskeletal pain, fatigue, and night sweats. There was a statistically significant association between side effects and daily living habits, treatment prior to HT and calcium replacement. Thus, we conclude that regarding HRQL, both general and specific, all subgroups had at least one significant correlation with the domains of the scales.